Demographic Factors and Truancy Behaviour among Secondary School Students in Ilorin Metropolis, Kwara State - Elizabeth Ronke Ehindero; Adekola Kamil Lasisi (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Background: Contemporary secondary school students exhibit a wide range of social maladjustment behaviours, especially truancy. Given this, the present study looked into the Demographic Factors Influencing Truancy Behaviour among Secondary School Students in Ilorin Metropolis, Kwara State. Method: The study used descriptive survey design with a multi-stage sampling procedure which involved purposive, stratified, and simple random methods. The research involved a total of 400 participants. The "Truancy Behaviour Scale (TBS)", was adapted to gather pertinent data. The instrument underwent validation by five seasoned lecturers specializing in Guidance and Counseling Educational Management and Test and Measurement. To assess the instrument's reliability, the researcher utilised the test Split-half method, yielding a reliability coefficient of 0.74. Demographic data was analyzed with frequency counts and percentages, and the four hypotheses formulated were tested using t-test and Analysis of Variance (ANOVA) at a significance level of 0.05. The findings show that demographic variables of student, family and school contributed significantly to truancy behaviour. The four null hypotheses tested in this study indicate that there was a significant difference in the demographic factors contributing to truancy behaviour among secondary school students in Ilorin metropolis, Kwara State, based on gender and family type (t = 2.88, p <0.05); (t = 2.56, p <0.05). Nonetheless, no significant differences were found based on the respondents' age and religion.